Effects of Neem (Azadirachta indica) Leaf Powder Supplementation on Rumen Fermentation, Feed Intake, Apparent Digestibility and Performance in Omani Sheep - Hani M. El-Zaiat; Elshafie I. Elshafie; Waleed Al-Marzooqi; Kawakob Al Dughaishi (Animals, 2022)
The objective of the present study was to evaluate the potential of the dietary addition of neem (Azadirachta indica) leaf powder (NLP) when compared to monensin (MON) on ruminal fermentation, feed intake, digestibility, and performance of growing lambs. Eighteen Omani lambs (22.8 ± 2.18 kg of body weight (BW)) were equally divided into three groups (n = 6 lambs/group) for 90 days. Animals were fed an ad lib basal diet consisting of Rhodes grass (Chloris gayana) hay (600 g/kg) and a concentrated mixture (400 g/kg) offered twice daily. Experimental treatments were control (basal diet without supplements); MON (control plus 35 mg/kg DM as a positive control); and NLP (control plus 40 g/kg DM). Lambs fed NLP had reduced ruminal ammonia nitrogen concentrations, protozoal counts, total volatile fatty acid, and blood urea nitrogen concentrations compared to the control. Compared to MON, lambs fed NLP had increased ruminal acetate and decreased propionate proportions. Inclusion of NLP in the diet increased blood total protein, globulin, and liver enzyme concentrations in comparison with the control, which was similar to MON. The lamb’s final BW and average BW gain were also increased with the NLP relative to the control. Further, adding NLP to the diet increased the digestibility of crude protein compared to the control diet. In conclusion, adding NLP to the diet with 40 g/kg DM could be used as a promising phytogenic supplement for growing lambs with no detrimental effects on the ruminal fermentation profile, nutrient intake, or digestibility.